The Catholic and Lutheran Joint Declaration on the Doctrine of Justification - Maffeis, Angelo (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2018)
Theology is structurally dependent on the tradition of faith and its languages that were often shaped by confessional controversies. How can a doctrinal consensus be reached between Churches that remain faithful to the faith witnessed by their traditions and at the same time are not caught by a mutually exclusive language? The article tries to give an answer presenting the method adopted by the Lutheran-Roman-Catholic dialogue on the justification, that in 1999 lead to the signing of the Joint Declaration on the Doctrine of Justification.